How can economic incentives designed for environmental conservation support a transition to sustainable and equitable agriculture? - Moros, L.; Puerto, S.; Monroy, D.; Achaval-Torre, J.; Rueda, X. (Commission on Sustainable Agriculture Intensification, 2021)
Agriculture is crucial for the livelihood of millions of people worldwide and is one of the main drivers of deforestation, biodiversity loss and resource degradation. The contribution of agriculture to these environmental problems has been exacerbated by subsidies, which constitute the dominant public policy to support farmers. At the same time, other economic instruments introducing more sustainable land-use practices and incentivizing better environmental and social outcomes are already being applied worldwide. In this report, we selected a set of these incentive-based instruments for conservation and reviewed synthesis and meta-analysis studies that offered robust evaluations and comparisons of existing research. Please note that we use conservation as a shorthand for the protection and restoration of nature, and the mitigation of the effects of climate change on the environment. Based on thisreview, we identify their impacts on environmental, economic, and equity outcomes and discuss the success factors and challenges in their application and design.